A influ??ncia da marca no efeito placebo: um quase-experimento em academias de gin??stica - Alves, Carlos Alberto (2014)
Research on the placebo (inert substances or procedures that may produce a desired effect) is not limited to the fields of psychology and medicine. In marketing, the placebo effect can be seen when a product that claims to have certain properties that it does not actually have and such claims change the attitude and especially the behavior of consumers. Few studies have been developed on this subject, in Brazil and abroad. This research study focused on the placebo effect applied to marketing, with the completion of two experiments that attempted to demonstrate the influence of the brand or brand extension on the placebo effect. For stimuli we used two extensions of recognized brands and two extensions of non-recognized brands of a protein bar and an isotonic drink, respectively. These were provided to two samples of 64 and 65 goers of gyms in the city of S??o Paulo. By analyzing the results, it was possible to confirm that groups with high motivation and high expectations tend to hold a more positive evaluation of brand extensions for both recognized and non-recognized products, through the perceived quality, price elasticity, purchase intention, and attitude. We also concluded that a brand or a brand extension may cause the placebo effect through subjective feelings of motivated consumers, leading to a change from their natural state. Although this study has achieved the desired goals, it presented limitations in scope, referring to the use of only two products for the experiments. Another perceived limitation relates to the method, the decision to employ quasi-experimental as the research design, which weakened the results from the point of view of internal and external validity. Important theoretical contributions of this work included a review of the brand as a result of the placebo effect identified through perceived quality, price elasticity, attitude, and intention to purchase quality, and the use of subjective sensations in the statement of the placebo effect on the marketing actions. This study is a pioneer in the simultaneous use of motivation and expectation as independent variables. The managerial contribution was to provide a broad spectrum of information about the placebo effect in marketing activities, so that the managers may apply it in promotional campaigns, pricing strategies, and decisions on brand management.